2014
DOI: 10.1097/01.ehx.0000446579.50830.b5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bone marrow-derived mesenchymal stem cells on the healing of experimental skin wound in diabetic adult male albino rats

Abstract: which wounded diabetic rats were treated with bone marrow-derived mesenchymal stem cells. Diabetes was induced in rats by means of a single intraperitoneal injection of streptozotocin. Wounds of groups III and IV were examined after 3 and 7 days. Skin specimens were processed and stained with H&E and Masson's trichrome. ResultsRe-epithelization with complete closure of the wound was noted in the stem celltreated group after 7 days. There was a significant increase in the number of hair follicles/high-power fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
(40 reference statements)
2
3
0
Order By: Relevance
“…(4) The prominent feature in the stem cell group was the presence of new blood vessels with well-defined endothelium. This finding coincides the study conducted by Mohammed et al (24) who reported that BM-MSCs promote healing in rats, with increased angiogenesis because of the raised level of growth factors and the endogenous signals that accelerate the healing. Moreover, BM-MSCs are capable of generating a huge number of endothelial cells both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 92%
“…(4) The prominent feature in the stem cell group was the presence of new blood vessels with well-defined endothelium. This finding coincides the study conducted by Mohammed et al (24) who reported that BM-MSCs promote healing in rats, with increased angiogenesis because of the raised level of growth factors and the endogenous signals that accelerate the healing. Moreover, BM-MSCs are capable of generating a huge number of endothelial cells both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 92%
“…The underlying dermis revealed disorganized collagen fibers and increased spaces between collagen fibers with invasion with inflammatory cells, these were in accordance with pervious research [24] . In confirmation to these results, the abnormalities in the formation of collagen protein at the wound area made healing process delayed and abnormal [20] .…”
Section: Discussionsupporting
confidence: 91%
“…These findings were explained by previous study which stated that disturbances in the functions of inflammatory cells (migration and phagocytosis), release of lytic proteases, increased production of reactive oxygen species and apoptosis. Also, diminished entrance of new blood vessels into the wound area leaded to further limitation of inflammatory cells functions [24] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations